The Kurds: An Encyclopedia of Life, Culture, and Society - Maisel, Sebastian (ABC-CLIO, 2023)
This indispensable resource for Western readers about the Kurds-an ancient indigenous group that exemplifies diversity in the Middle East-examines their history, politics, economics, and social structure. The Kurds: An Encyclopedia of Life, Culture, and Society provides an insightful examination the Kurds-from their historical beginning to today-through thematic and country-specific essays as well as important primary documents that allow for a greater understanding of the diversity and pluralism of the region. This single-volume work looks at the Kurds from a variety of angles and disciplines, including history, anthropology, economics, religion, geography, and musicology, to cover the ethnic populations of the original Kurdish homeland states as well as of the diaspora. The book evaluates sources in Kurdish (both Kurmanci and Sorani) in addition to information of Arabic, Persian, and Turkish origin to present broad, up-to-date coverage that will serve nonspecialist readers, high school and college students, and professionals, journalists, politicians, and other decision makers who require accurate perspectives on Kurdish history and culture. Additionally, an entire section of the book provides excerpts of primary sources selected for their importance to Kurdish history and identity. These 20 primary source excerpts are accompanied by introductions and analysis that enable readers to fully appreciate their political, religious, and cultural importance